Nursing students' commitment and the mediating effect of stress. (May 2019) - Riley, Jason M.; Collins, Desiree; Collins, Jamie
Abstract: Objectives: Knowing there is a shortage of qualified nurses throughout the healthcare industry, it is imperative that program administrators understand the factors that affect nursing students as they select and commit to their academic major. They should consider key influences on potential students as new recruiting and retention tactics are developed and employed. Thus, we develop the current study to understand factors that shape students' commitment to nursing. Specifically, we attempt to discern how potential career growth, students' understanding of available occupational specialties, family members, and instructors affect nursing students' commitment to their chosen academic program. In addition, we analyze the mediating effect of stress in order to explain why some factors have more influence than others do. By conducting this research, we hope to provide insight into how to better recruit potential students and retain existing students already enrolled in nursing programs. Design/setting/methods: Data collection took place in 2016 at one public and one private nursing program. The sample is understanding of available occupational specialties of 167 nursing student who completed a structured survey. Career growth, occupational specialties, instructors' and family influence were measured to understand how they affected major commitment and by extension intention to stay with their nursing program. We also assessed the potential mediating effect of stress on students' commitment to the nursing major. Ordinary least squares regression (SPSS version 22) was then used to evaluate both direct and mediated relationships. Results: Based on the analysis, potential career growth, students' understanding of available occupational specialties, and family members directly affect nursing students' level of commitment to their chosen academic major. Results indicate that when students learn about the growth potential of the nursing profession or the different occupational specialties available that they will be more committed to the chosen major. The students likely believe the nursing profession aligns with their personal ambitions and skillsets. In addition, results indicate that stress fully mediates the level of commitment a student has towards nursing as an academic major. Evidence from the nursing students in this study indicates that their level of commitment to nursing programs is harmed by high levels of experienced stress. Students may feel that they identify with this area of study, but if they are stressed they may believe they lack the necessary abilities to succeed and/or perceive the nursing profession as undesirable to them personally. Conclusion: Understanding factors that influence students' commitment to an academic major is important to administrators as they work to improve the number of students enrolled in accredited nursing programs. Specifically, they can use insights from this study to better develop recruitment and retention programs by enabling students to garner feelings of pride, enthusiasm, and positively identify with the nursing profession.